2019
DOI: 10.1002/anie.201910489
|View full text |Cite
|
Sign up to set email alerts
|

Crystalline Cooperativity of Donor and Acceptor Segments in Double‐Cable Conjugated Polymers toward Efficient Single‐Component Organic Solar Cells

Abstract: The crystalline cooperativity of the donor and acceptor segment in double‐cable conjugated polymers plays an important role in the nanophase separation and photovoltaic performance in single‐component organic solar cells (SCOSCs). Two double‐cable conjugated polymers with the same conjugated backbone and perylene bisimide (PBI) side units were designed in which PBIs were positioned symmetrically and perpendicularly (P1) and asymmetrically and slantingly (P2) along the conjugated backbones. After thermal anneal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 40 publications
(12 reference statements)
1
43
0
Order By: Relevance
“…From atomic force microscopy measurement, it clearly showed that the optimized JP01 and JP02 thin films had relatively low roughness with small domain size (Supporting Information, Figure S8 b and Figure S9 b), indicating that better nanophase separation between backbones and NDIs could be obtained. Similar phenomenon could also be observed in our previous study, in which good crystalline cooperativity was linked to good nanophase separation [7k] . Further studies by GIWAXS revealed that these optimized thin films had relatively high CLs of q 2 / q 001 and q 010 peaks, corresponding to the better molecular packings (Supporting Information, Figure S10 and Table S9).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…From atomic force microscopy measurement, it clearly showed that the optimized JP01 and JP02 thin films had relatively low roughness with small domain size (Supporting Information, Figure S8 b and Figure S9 b), indicating that better nanophase separation between backbones and NDIs could be obtained. Similar phenomenon could also be observed in our previous study, in which good crystalline cooperativity was linked to good nanophase separation [7k] . Further studies by GIWAXS revealed that these optimized thin films had relatively high CLs of q 2 / q 001 and q 010 peaks, corresponding to the better molecular packings (Supporting Information, Figure S10 and Table S9).…”
Section: Resultssupporting
confidence: 87%
“…We have been particularly interested in double‐cable conjugated polymers for application in SCOSCs since they could be synthesized via a controllable manner, in which a series of functionalized monomers with pendent electron acceptors were prepared for palladium‐catalyzed polymerization [11] . This enabled us to incorporate the widely reported conjugated polymers and electron acceptors into double‐cable polymers, providing tunable optical and electrical properties [7h–m, 12] . Among them, we found that the linear conjugated backbones [7h] and post‐thermal treatment [7i] could facilitate the simultaneous self‐assembly of conjugated backbones and aromatic side units, generated well‐ordered nanophase separation, and hence provided external quantum efficiencies (EQEs) above 0.65 and PCEs over 6 %.…”
Section: Introductionmentioning
confidence: 99%
“…The control of aggregated structure of the polymer acceptors, [405][406][407][408][409][410] double-cable polymers [411][412][413][414] and multicomponent polymer blends remains a critical hurdle. These complex material systems may exhibit different aggregation behaviors, remaining challenges for controlling the aggregated structure of corresponding systems.…”
Section: Morphology Control Strategies For Complex Materials Systemsmentioning
confidence: 99%
“…In the past 5 years, PCEs of 12–16% have been achieved in various NFAs cases via rational designing of the A and D unit chemical structures. [ 1,39–48 ] Very recently, the efficiency has been pushed to ≈18% owing to the development of novel NFAs (Y6 and derivatives) and efficient polymer donors. [ 49 ] Consequently, with the continuous development of efficient photoactive materials, significant progress has been achieved for flexible OSCs in recent years.…”
Section: Introductionmentioning
confidence: 99%